Forecasting foreing exchange reserves using Bayesian Model Averaging-Naïve Bayes - Salas-Compás, María Belén; Alaminos Aguilera, David; Fernández-Gámez, Manuel Ángel; Callejón-Gil, Ángela (World Scientific, 2020)
Foreign exchange reserves are used by governments to balance international payments and make stable the exchange rate. Numerous works have developed models to predict foreign exchange reserves; however, the existing models have limitations and the literature demands more research on the subject given that the accuracy of the models is still poor, and they have only been used for emerging countries. This paper presents a new prediction model of foreign exchange reserves for both emerging countries and developed countries, applying a method of Bayesian model averaging-Naïve Bayes, which shows better precision results than the individual classifier. Our model has a great potential impact on the adequacy of macroeconomic policy against the risks derived from balance of payment crises providing tools that help to achieve financial stability on a global level.
Keywords: Balanza de pagos; Foreing exchange reserves; Balance of payment; Bayesian model averaging; Naïve Bayes; Forecasting